EXPERIENCE OF USING MECHANICAL THROMBECTOMY IN A PATIENT WITH SEVERE STROKE AND SEVERE COMORBID PATHOLOGY TAKING ANTICOAGULANTS - Марина Анатольевна Пеганова; Елена Алексеевна Полукарова; Александра Константиновна Волкова; Сергей Николаевич Филимонов; Светлана Станиславовна Зиборова; Елена Сергеевна Грязнова; Максим Алексеевич Верещагин (Медицина в Кузбассе, 2022)
Emergency reperfusion is the main method of treatment in the most acute period of acute cerebrovascular accident. To date, several methods of therapy are used: intravenous thrombolytic therapy, intravascular thrombectomy. The ability to choose from these methods allows you to develop an effective treatment strategy, taking into account the individual characteristics of the patient.